THE EFFECTS OF INQUIRY TRAINING ASSIST MEDIA OF HANDOUT AND ATTITUDE SCIENTIFIC TOWARDS SCIENCE PROCESS SKILLS IN PHYSICS STUDENTS - Halimatus Sakdiah; Sahyar . (Universitas Negeri Medan, 2014)
The purpose of this research has described difference: (1) skill of student science process between inquiry training assist media of handout and direct instruction, (2) skill of student science process between student possess attitude scientific upon and under of mean, and (3) interaction of inquiry training assist media handout and direct instruction with attitude scientific increase skill of student science process. Type of this research is experiment quasi, use student of senior high school Private sector of Prayatna as population and chosen sample by cluster sampling random. The instrument used essay test base on skill of science process which have valid and reliable. Data be analysed by using ANAVA two ways. Result of research show that any difference of skill of student science process (1) between inquiry training assist media of handout and direct instruction, where inquiry training assist media of handout better then direct instruction, (2) between student possess attitude scientific upon and under of mean, where possess attitude scientific upon of mean better then student possess attitude scientific under of mean and (3) any interaction between inquiry training assist media of handout and direct instruction with attitude scientific increase skill of student science process, where interaction in class direct instruction better then inquiry training assist media of handout.